Digital Public Relations Strategy for Muhammadiyah Cadreization: Evidence from Instagram @mpksdi_ppm - Sumarlan, Iman; Hakim, Lukman; Priadi, Arum (Universitas Muhammadiyah Yogyakarta, 2026)
The rapid development of digital communication technologies has transformed public relations practices in organizational communication. Social media platforms enable organizations to interact directly with audiences, disseminate institutional values, and strengthen relationships with stakeholders. This study examines digital public relations practices in Muhammadiyah’s cadreization communication through the Instagram account @mpksdi_ppm. The research aims to identify patterns of digital public relations communication, map strategic principles supporting Muhammadiyah’s cadreization process, and analyze factors influencing the effectiveness of cadreization content on social media. This study employed a qualitative exploratory approach using digital content observation, in-depth interviews, and documentation analysis. Data were collected through interviews with seven informants, including social media managers, organizational leaders, Instagram followers, and representatives of Muhammadiyah regional organizations. Observations were conducted on social media management and content production processes at the office of the Council for Cadre Development and Human Resources of Muhammadiyah (MPKSDI). The findings reveal three main strategic principles of digital public relations: value-based messaging, visual storytelling, and audience engagement. Instagram functions not only as a documentation platform but also as a strategic communication channel for disseminating ideological values and strengthening Muhammadiyah cadre identity. Digital public relations practices contribute to expanding communication reach, facilitating knowledge dissemination among cadres, and reinforcing Muhammadiyah’s institutional identity in the digital environment